2018
DOI: 10.1002/er.4245
|View full text |Cite
|
Sign up to set email alerts
|

Modeling cooperative creep reoxidation effect on the mechanical stability of anode-supported solid oxide fuel cell

Abstract: Summary Mechanical stress which develops during redox or creep of nickel‐doped yttria‐stabilized zirconia (Ni‐YSZ) anode has been widely recognized as an important limitation for structural stability and commercialization of solid oxide fuel cell (SOFC). In this paper, the cooperative effect of reoxidation after creep (termed creep reoxidation) arising from abnormal operation condition on the mechanical robustness of SOFC is studied. In order to simulate inhomogeneous oxidation of Ni‐YSZ at operation temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Since SOFC operates at high temperatures, the mechanical failure stimulated by thermal stress is serious . Researchers usually used numerical methods to examine the thermal stress characteristics of different SOFC structures, including single channel units, single cell and cell stack.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since SOFC operates at high temperatures, the mechanical failure stimulated by thermal stress is serious . Researchers usually used numerical methods to examine the thermal stress characteristics of different SOFC structures, including single channel units, single cell and cell stack.…”
Section: Introductionmentioning
confidence: 99%
“…6 Since SOFC operates at high temperatures, the mechanical failure stimulated by thermal stress is serious. [7][8][9] Researchers usually used numerical methods to examine the thermal stress characteristics of different SOFC structures, including single channel units, single cell 10,11 and cell stack. Xu et al 12 evaluated the stress distribution under different interconnect-electrode contact area through a single channel model and they found that a larger contact area can effectively reduce the first principle stress close to the corner of interconnect-cathode contact region at the fuel inlet.…”
mentioning
confidence: 99%
“…The fuel of SOFCs can be hydrogen, 1 methane, 2 and wheat straw 3 . This advanced power generation technology has high efficiency and low pollution and emission but requires high operating temperature (600°C‐800°C), which will lead to problems of sealing failure, 4 creep, 5 degradation, and fracture. Micro‐cracks will also be generated and propagated owing to high thermal mismatch and elastic mismatch.…”
Section: Introductionmentioning
confidence: 99%
“…If the mechanical performance of a battery pack casing cannot meet the requirements of real application, it may result in the short circuit even explosion or more severe accidents . Therefore, the mechanical performance of a battery pack casing is significant for batteries, electric vehicles, and road safety . In addition, lightweight is also considered as an objective which is necessary for less volume consumption and more extended driving range.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, interface thermal stress also affects the stabilization and endurance of solid oxide fuel cell. Xie et al proposed a thermomechanical model of solid oxide fuel cell considering the interfacial layer, which was conducted to analyze the interfacial thermal stresses between electrodes and electrolyte. This model was proved to be effective to determine and minimize the interfacial thermal stresses of solid oxide fuel cell.…”
Section: Introductionmentioning
confidence: 99%